Arlequina e sua emancipação fantabulosa nas telas do cinema: a importância da caracterização para o empoderamento de personagens femininas - Izabela Louzada Amaral Rocha (2024)
Characterization is a fundamental language for audiovisual products, from which it is possible to read different aspects of the character, from their social class, age range and even personal tastes. Since the beginning of cinema, costumes and accessories, hair, makeup, and props have been used to identify and distinguish characters. On Halloween 2015, Harley Quinn‘s costume from the Suicide Squad (2016) movie was the most searched costume on internet by the American women, even before the movie premiere, raising the discussion on this master thesis. However, her characterization promotes questions about women‘s representation in media, placing them as a product for the male public consumption. This research aims to explain the importance of characterization for the character developing and the audience; identify Harley Quinn‘s characterization conception in movies relating to her cartoon and videogames appearances; and to question costume choices that perpetuate sexist behaviors which objectify and sexualize women.